Competing in the new world of work : how radical adaptability separates the best from the rest - Ferrazzi, Keith; Gohar, Kian; Weyrich, Noel (Boston, Massachusetts : Harvard Business Review Press, 2022)
"The #1 New York Times bestselling author and longtime leader in the discussion of the future of work provides research-based insights and best practices for leading change in the ever-evolving post-pandemic world of work. The pandemic forced your organization to shed antiquated systems, processes, and procedures and to make a bold leap into an even more digitally enabled, technology-driven future. After months of adapting, your teams have settled into new, often better, ways of doing things. But there isn't yet a shared base of knowledge of what's worked, what hasn't, and what could work better as companies reinvent everything they do-or how they can emerge stronger and leap ahead farther coming out of the pandemic and beyond. Which new practices, adopted in response to the crisis, are here to stay and will go forward into the post-pandemic era? How are leaders reshaping their organizations for a different, post-Covid world? How do these new practices and behaviors add up to a new playbook for success? New York Times bestselling author Keith Ferrazzi offers a bold new vision for what the organization of the future looks like-digital, distributed, inclusive, resilient, empathic-and the emerging best leadership practices that will redefine success in the ever-evolving world of work. Based on an ambitious global research initiative involving thousands of executives, innovators, and changemakers who have redefined their strategies, business models, organizational systems, and even their cultures, this book documents the workplace innovations that emerged during the pandemic and shows leaders how to shape their organizations and practices to remain competitive in a new, post-pandemic context. Competing in the New World of Work offers leaders the inspiration and the road map to catapult their organizations forward, make up for lost time, embrace new realities, and win new frontiers"--
Radical adaptability -- Collaborate through inclusion -- Lead through Enterprise Agile -- Promote team resilience -- Develop active foresight -- Future-proof your business model -- Build a Lego block workforce -- Supercharge your purpose.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed April 11, 2023).
WorldCat record variable field(s) change: 050
Keywords: Organizational change; Organizational effectiveness; COVID-19 Pandemic, 2020- -- Economic aspects; Industrial management; Success in business; Organizational behavior; Organizational Innovation; Changement organisationnel; Efficacité organisationnelle; Pandémie de COVID-19, 2020- -- Aspect économique; Gestion d'entreprise.; Succès dans les affaires; Comportement organisationnel; Economics; Industrial management; Organizational behavior; Organizational change; Organizational effectiveness; Success in business